2017
DOI: 10.1177/1538192717709584
|View full text |Cite
|
Sign up to set email alerts
|

The Validation Function of a Sustained Orientation and Transfer Program: A Longitudinal Qualitative Study

Abstract: This study longitudinally examined the experiences of four different student cohorts who participated in Adelante, a sustained orientation/transfer program designed to assist students in the transfer process from the community college to a baccalaureatedegree granting university. The researcher found that students positively perceived the services, structure, social networking environment, and early exposure to careers. The study provides evidence for the validation function of sustained orientation programs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…These transfer rates are notably higher than the national rate of 14% among Latinx community college students (Velez, 2016). In a separate study, Latinx students that participated in a transfer program reported that many of the resources and services offered by the program were very useful in helping them persist, graduate, and transfer to a 4-year college (Andrade, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These transfer rates are notably higher than the national rate of 14% among Latinx community college students (Velez, 2016). In a separate study, Latinx students that participated in a transfer program reported that many of the resources and services offered by the program were very useful in helping them persist, graduate, and transfer to a 4-year college (Andrade, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Staff and faculty practices positively influenced Latinx student persistence and transfer. Counselors provided Latinx students with useful information about the transfer process and requirements to persist (Andrade, 2019). Constant reminders also helped Latinx students stay on track to transfer (Andrade, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations